Pendekatan Studi Kritis dan Relevansinya Terhadap Kebijakan Publik - Rizkwanti, Robertha Astri Karunia Dewi; Caspari, Andrean (Universitas Airlangga, 2024)
Public policymaking is a lengthy process influenced by various factors before reaching the implementation stage. Meanwhile, critical theory studies aim to encourage changes in the social order based on democratic, emancipatory, and humanitarian impulses. In line with this encouragement, the concepts of critical theory from the Frankfurt School, such as alienation, reification, and emancipation, can be used to explain social phenomena that arise during policy implementation. Taking the example of Law No. 6 of 2014 about Village Governance, the author will dissect the problems that arise as policy implementation progresses. Based on existing findings, obstacles in the process of making and implementing policies often arise as a consequence of policies that reduce village residents to objects rather than subjects. By examining these problems in villages, it is hoped that this analysis can provide valuable input and consideration for policymakers, especially in the discourse on revising village laws. Keywords: Critical Theory, Alienation, Reification, Emancipation, Public Policymaking, Village Law